Diagnosis and Development Perspectives of Open Pension Funds - Olejnik, Iwona (Ekonomika, 2008)
Within the last few years, the interest in the issues of the systems that are to provide financial security in old age has increased, while the inefficiency of pension systems is more and more often perceived as a global problem. The erosion of pension systems is visible mainly in the countries that transformed their economies into market-based ones. An efficient and effective construction of social security systems to prevent the effects of an increased risk of old age has become an important goal of social policy in numerous countries. In this relation, many countries, not only European ones, have carried out pension reforms but still many face the necessity of changing their pension systems. The aim of the paper is, therefore, a synthetic presentation of selected aspects of the current development of one of the elements of pension systems, i. e. open pension funds, and the problems that accompany this development, basing on the example of one of the countries of Central Europe, namely Poland. Also, the perspectives for the development of these funds are presented.The paper contains, inter alia, the results of a representative questionnaire research carried out in 2007 among the customers of pension funds, as well as among the experts on the financial system in Poland. It seems that Polish experience related to the introduction of pension funds to the Polish market in 7999 and the numerous positive phenomena that accompany their development may constitute one of the patterns for implementing reforms and introducing pension funds in other countries.